(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
the article describes the need, opportunities and ways to accelerate innovative activity in service sector enterprises. Also, specific problems of developing this industry on an innovative basis and measures to eliminate them are justified.